Low‐grade serous ovarian carcinoma: A comprehensive literature review. (17th December 2019) - Goulding, Elizabeth A.; Simcock, Bryony; McLachlan, Jennifer; van der Griend, Rachael; Sykes, Peter
Abstract : Background: Low‐grade serous ovarian carcinoma (LGSOC) is a unique entity with clinical and molecular characteristics distinct from high‐grade serous ovarian carcinoma (HGSOC). To date the majority of research has focused on the more common HGSOC, with treatment recommendations often extrapolated to LGSOC. Women with LGSOC are typically diagnosed younger and have indolent and relatively chemoresistant disease. Recently there have been major research advances in LGSOC. Aims: This systematic review describes the epidemiological, clinical and molecular characteristics of LGSOC, with advances in research and novel treatment options also discussed. Materials and Methods: A 10‐year comprehensive systematic review of peer‐reviewed literature was conducted, with a total of 132 abstracts read, 89 articles reviewed and 49 included in this review. Results: This review highlights the clinical and molecular features of LGSOC, current and traditional treatment options and areas of current research into targeted agents. Conclusions: Our growing knowledge about LGSOC as a distinct clinical and molecular entity from HGSOC has led to the investigation of more targeted and tailored therapies as their clinical course, optimal management and therapeutic targets differ. There is a need for ongoing collaborative research to provide better treatment options for these patients.